An investigation into the changing workplace of South African auditors and their experiences of Artificial Intelligence (AI) systems and the implications for the auditing profession - BONNIN, DEBBY (University of Pretoria, 2024)
Dissertation (MSocSci (Industrial Sociology and Labour Studies))--University Of Pretoria, 2023.